Head and neck imaging - Som, Peter M.; Curtin, Hugh D. (Elsevier, 2011)
Features imaging examples that help you recognize the imaging presentation of the full range of head and neck disorders using PET, CT, MRI, and ultrasound. This title covers the complexities of embryology, anatomy, and physiology, including anatomical images that help you distinguish subtle abnormalities and understand their etiologies